An Analysis of Legal Concepts Concerning Abortion Case According to Criminal Code and Law No.36 of 2009 Concerning Health - SARAGI, PALTIADA (The journal of contemporary issues in business and government, 2021)
Abortion practice has now become an actual phenomenon that can occur everywhere. The number of deaths due to abortion is very appalling and alarming. Based on data from World Health Organization (WHO), it is stated that 15-50% death of mother was resulted from miscarriage on purpose, which is not very safe. Under our law (hukum positif) particularly in Indonesia, abortion acts in some cases can be justified if it only relates to abortus provocatus medicinal condition. On the contrary, an abortion act which is generalized might become a criminal act that is commonly known as abortus provocatus criminalis. In this thesis, the writer discusses the problems concerning the concept of the law related to abortion criminal act pursuan to Indonesian Penal Law (KUHP) and Health Act No. 36 year 2009 using descriptive analysis method which does not apply hypothesis or testing a theory. This research originates from the idea that there are problems related to concept and actual law implementation concerning abortion as a criminal act based on our Penal Law (KUHP) and Health Act No. 36 year 2009. The analysis concept law meant in this thesis is to peruse Indonesian Penal Law and Acts No. 36 year 2009 concerning abortion as criminal act. The writer uses secondary data which is comprised of primary material, secondary and tertiary law. on the findings and discussion, it is concluded that the application of Indonesian Penal Law and Health Act as ground or standing of the law to become Judge’s own consideration has yet to be realized or applied consistently to abortion as criminal act. In addition, it appears that there is a lack of enforcement of the law on the part of the law enforcer agency in resolving abortion-related problems and thus contributing to the problematic and debatable status of abortion.